Desmistificando as criptomoedas: a contribuição das moedas virtuais na diversificação dos investimentos - Silveira, Leticia Moraes (2021)
Within the wide range of available financial assets are cryptocurrencies or virtual currencies. This financial innovation is based on encryption and all its transactions are recorded and stored digitally by a technology that shares accounting data, known as blockchain. In this context, the study’s objective was to verify the contribution of virtual currencies in the investments’ diversification and was based on the portfolio’s theory of Markowitz (1952). This diversification between assets can be specific to each case, according to the levels of risk preferred by the investor's aversion or affinity. Therefore, five portfolio composition models were selected: average variance, average semi variance, expected loss, average absolute deviation and omega. The sample was divided into 5 sub-samples in order to avoid bias and provide greater robustness to the results. Each sub-sample consisted of 100 shares and 5 cryptocurrencies. The cryptocurrencies used in this research were Bitcoin, Ethereum, Ripple, Litecoin and Stellar. The period was delimited from January 18, 2017 to March 30, 2021. Also, an additional analysis of the assets’ behavior in the portfolios was carried out, considering the periods before and after the beginning of the COVID-19 pandemic. The results showed that Bitcoin was the cryptocurrency with the most consistent performance, participating in most portfolios in all periods analyzed. However, Ethereum and Ripple also showed good results. Litecoin did not obtain consistent results, as it was selected from only one portfolio in the post-pandemic period. Stellar was the only cryptocurrency that was not selected for the portfolio’s composition in any of the applied methodologies. Thus, is confirm that cryptocurrencies can generate diversification benefits and contribute to investments’ return when allocated by investors in their portfolios.